Immunoregulatory Functions of Interferons During Genital HSV-2 Infection - Feng, Emily; Balint, Elizabeth; Vahedi, Fatemah; Ashkar, Ali A. (Frontiers in Immunology, 2021)
Herpes simplex virus type 2 (HSV-2) infection is one of the most prevalent sexually transmitted infections that disproportionately impacts women worldwide. Currently, there are no vaccines or curative treatments, resulting in life-long infection. The mucosal environment of the female reproductive tract (FRT) is home to a complex array of local immune defenses that must be carefully coordinated to protect against genital HSV-2 infection, while preventing excessive inflammation to prevent disease symptoms. Crucial to the defense against HSV-2 infection in the FRT are three classes of highly related and integrated cytokines, type I, II, and III interferons (IFN). These three classes of cytokines control HSV-2 infection and reduce tissue damage through a combination of directly inhibiting viral replication, as well as regulating the function of resident immune cells. In this review, we will examine how interferons are induced and their critical role in how they shape the local immune response to HSV-2 infection in the FRT.